2004
DOI: 10.1086/381779
|View full text |Cite
|
Sign up to set email alerts
|

The Nonlinear Alfvn Wave Model for Solar Coronal Heating and Nanoflares

Abstract: The mechanism of solar coronal heating has been unknown since the discovery that the coronal plasma temperature is a few million degrees. There are two promising mechanisms, the Alfvén wave model and the nanoflare-reconnection model. Recent observations favor the nanoflare model since it readily explains the ubiquitous small-scale brightenings all over the Sun. We have performed magnetohydrodynamic (MHD) simulations of the nonlinear Alfvén wave coronal heating model that include both heat conduction and radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 29 publications
2
103
0
Order By: Relevance
“…In particular, the effects of heating, radiation, and conduction were first studied by Mariska & Hollweg (1985), and the effects of a body force were originally discussed by Sterling & Hollweg (1988). The model has been applied to both linear and nonlinear problems in various solar and stellar contexts (Sterling & Hollweg 1984;Mariska & Hollweg 1985;Kudoh & Shibata 1997;Moriyasu et al 2004;Fujita et al 2007;Musielak et al 2007;Antolin & Shibata 2008).…”
Section: Model and Governing Equationsmentioning
confidence: 99%
“…In particular, the effects of heating, radiation, and conduction were first studied by Mariska & Hollweg (1985), and the effects of a body force were originally discussed by Sterling & Hollweg (1988). The model has been applied to both linear and nonlinear problems in various solar and stellar contexts (Sterling & Hollweg 1984;Mariska & Hollweg 1985;Kudoh & Shibata 1997;Moriyasu et al 2004;Fujita et al 2007;Musielak et al 2007;Antolin & Shibata 2008).…”
Section: Model and Governing Equationsmentioning
confidence: 99%
“…These phase relations should be taken into account in the estimation of observational manifestation of torsional waves in twisted and possibly rotating plasma structures, e.g. in the gyrosynchrotron emission by the fashion similar to applied by Tapping (1983) to torsional modes and Nakariakov & Melnikov (2006) to longitudinal modes of straight non-rotating flux tubes. Also, these relations should be used in forward modelling of torsional waves observed with spectrometers.…”
Section: Compressibility Of the Torsional Modementioning
confidence: 99%
“…Ruderman 1999;Copil et al 2008). In particular, Moriyasu et al (2004) and Antolin et al (2008) paid special attention to nonlinear effects and shock formation. It was demonstrated numerically that the observed spiky intensity profiles due to impulsive energy releases could be obtained from nonlinear torsional waves.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusive acceleration of particles by MHD waves was contrasted and compared to direct E-fields and shocks formed by large scale current sheets in the break-up model. Several recent articles showed that the non linear evolution of the MHD waves form small scale structures, which act also as shocks or UCS [23,22,24].…”
Section: The Loop Modelmentioning
confidence: 99%